Global epidemiology of Mycobacterium tuberculosis lineage 4 insights from Ecuadorian genomic data - Gabriel Morey-León; Paulina M. Mejía-Ponce; Juan Carlos Fernández-Cadena; Evelyn García-Moreira; Derly Andrade-Molina; Cuauhtémoc Licona-Cassani; Pablo Fresia; Luisa Berná (Scientific Reports)
Abstract Tuberculosis is a global public health concern, and understanding Mycobacterium tuberculosis transmission routes and genetic diversity of M. tuberculosis is crucial for outbreak control. This study aimed to explore the genomic epidemiology and genetic diversity of M. tuberculosis in Ecuador by analyzing 88 local isolates and 415 public genomes from 19 countries within the Euro-American lineage (L4). Our results revealed significant genomic diversity among the isolates, particularly in the genes related to protein processing, carbohydrate metabolism, lipid metabolism, and xenobiotic biodegradation and metabolism. The population structure analysis showed that sub-lineages 4.3.2/3 (35.4%), 4.1.2.1 (22.7%), 4.4.1 (12.7%), and 4.1.1. (10.7%) were the most prevalent. Phylogenetic and transmission network analyses suggest that these isolates circulating within Ecuador share genetic ties with isolates from other continents, implying historical and ongoing intercontinental transmission events. Our findings underscore the importance of integrating genomic data into public health strategies for tuberculosis control and suggest that enhanced genomic surveillance is essential for understanding and mitigating the global spread of M. tuberculosis. This study provides a comprehensive genomic framework for future epidemiological investigations and control measures targeting M. tuberculosis L4 in Ecuador.